When size meets skill: the surgical ordeal of a giant retroperitoneal liposarcoma - Sreekanth, K.; Balmoori, Nived R.; R., Arun Sundara Rajan A.; Sai, Chilukuri Ramananda; Choudhary, Yalavarthi Soha (International Surgery Journal, 2025)
Retroperitoneal liposarcomas represent an uncommon subset of soft tissue sarcomas, typically exhibiting an indolent growth pattern and remaining clinically silent until attaining a size sufficient to exert mass effect on adjacent organs. Lesions measuring 30 cm or more in maximal diameter are exceedingly rare, with only a limited number of such cases documented in the literature. This report presents a 32-year-old woman from Zambia presented with a history of progressive abdominal distension over the past eight years. She had been diagnosed with a retroperitoneal liposarcoma and was referred to our centre for further management. Contrast-enhanced computed tomography (CT) of the abdomen and pelvis revealed a large, predominantly fat-density lesion arising from the right retroperitoneum, measuring approximately 194×274×301 mm. The mass occupied most of the abdominal and pelvic cavities, encasing and displacing the right kidney, proximal ureter, and renal vessels. The right adrenal gland was also encased, and the bowel loops were displaced toward the left side. The duodenum, ascending colon, pancreas, and inferior vena cava (IVC) were displaced superiorly and to the left, with the lesion abutting the inferior surface of the liver. Complete surgical excision of the retroperitoneal tumour was achieved, including an en bloc right nephrectomy. Massive retroperitoneal liposarcoma is an extremely rare neoplasm with a high risk of recurrence, influenced by factors such as histological subtype, tumour grade, presence of metastases, and completeness of surgical excision. In the present case, a complete resection was achieved, including an en bloc right nephrectomy. The patient will be monitored closely with periodic clinical and radiological follow-up to enable early detection of any recurrence.